Improving Teacher’s Performance through Principal’s Supervision - Arianti, Nini; Perrodin, David D; Maulina, Dina; Suarman, Suarman; Ekawarna, Ekawarna; Danim, Sudarwan (PPSDP International Journal of Education, 2022)
The purpose of this study was to discover how the stages of principal’s supervision improved teacher performance at SD Negeri 245 Palembang. The qualitative technique was employed with observation, interviews, and documentation as tools. Miles and Huberman's theory was used to examine the data. The results revealed that (1) the supervision program is prepared and implemented at the start of each school year, and (2) supervision assessment is carried out at the conclusion of each semester by notifying instructors personally and in groups. This study has received little attention since it investigates supervision in depth in order to improve teacher effectiveness in primary schools. This study is designed to benefit school principals by enhancing performance connected with principal’s supervision.